BEBERAPA FAKTOR PENENTU KEBERHASILAN IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI MANAJEMEN DAERAH - Tawaris, Mario; Sondakh, Telly; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : North Halmahera regency administration, particularly BAPPEDA Astra Honda Motor as an object of study HAS husband has a Regional Management Information System (SIMDA) Computer-Based, although still partial. Clearly, not available yet compatible hearts The Information Technology supports Implementation Tasks Implementation Process Planning and Regional Planning Program Activity. It alleged ADA husband Operative factors determining the success or failure of a significant policy Implementation of Regional Management Information Systems The ADA in BAPPEDA. The taxable income is to identify variables Research, then known that the distribution of respondents Against ALL variables, either free or prepaid variable Bound variables / not free prepaid, Pretty Varied. Operates partial, free prepaid variables (resources, disposition OR ATTITUDE And strukrtur Bureaucracy) bepengaruh positive and significant success against policy implementation SIM AT BAPPEDA North Halmahera. Operate Together, All free prepaid variable (communication, resources, disposition / ATTITUDE And Bureaucratic Structure) significant positive effect And Against The success of policy implementation SIM AT BAPPEDA North Halmahera. Given the significance of the influence of communication yet Against the successful implementation of Management Information Systems pada BAPPEDA District North Halmahera, then Leaders Need to Establish Communication Effective prayer Directions Yang Hobbies, both among the leadership level, between subordinates and leadership BETWEEN THE subordinates. Keywords: Implementation, Management Information Systems Area.